Multilingual multimodal integration of sketch and speech: A generic speech representation model for spatial description - Lee-Na, Teh; W. Yeo, Alvin (IEEE, 2009)
This paper details how multiple languages are accommodated in the multimodal integration of sketch and speech, specifically, in spatial applications. The study encompasses English, Malay, Mandarin, and two under-resourced languages in Malaysia, i.e. Melanau and Iban. The preliminary study revealed that not all spatial terms (prepositions) appear in all languages. Based on these findings, we propose a method to assist in the design and development of multilingual multimodal applications. This method employs a generic representation model for spatial description.